Forecasting Kuantitas Penjualan Herbisida dengan Metode SES pada UD.Central Tani - Rini Wahyuni; Zulfi Azhar; Edi Kurniawan (J-Com (Journal of Computer), 2021)
Abstract :  UD.Central Tani which is located in Sei Sentang Village, Jalan Pusat Pasar 7, Kualuh Hilir District, North Labuhanbatu Regency, is one of the trading businesses that is developing in the pesticide industry. UD.Central Tani not only sells pesticides but also sells fertilizers, fish food, corn seeds and others. For its own stock, UD.Central only supplies fertilizers and herbicides based on estimates, so there are often shortages and oversupply. Therefore, to determine the sales target to be achieved by paying attention to sales conditions in the past. Sales information is needed so that it can help forecasting the sale of herbicides so that the stock of herbicides in the business can be well controlled. Therefore we need a system that can help predict herbicide sales from time to time. So with the resulting forecasting results, it is expected to help sales in accordance with existing conditions. The method that will be used for research is the Single Exponential Smoothing method. Keywords: Sales; forecasting; pesticides; single exponential smoothing; system.  Abstrak : UD.Central Tani yang bertempat Desa Sei Sentang Jalan Pusat Pasar 7 Kecamatan Kualuh Hilir Kabupaten Labuhanbatu Utara merupakan salah satu Usaha Dagang yang berkembang dalam industri pestisida. UD.Central Tani tidak hanya menjual pestisida tetapi juga menjual pupuk, makanan ikan, bibit jagung dan lainnya. Untuk stoknya sendiri UD.Central hanya menyetok pupuk dan herbisida berdasarkan perkiraan saja sehingga sering terjadi kekurangan dan kelebihan pasokan. Maka dari itu untuk menentukan target penjualan yang ingin dicapai dengan cara memperhatikan kondisi penjualan di masa lalu. Informasi penjualan sangat dibutuhkan agar dapat membantu peramalan dalam penjualan herbisida supaya stok herbisida pada usaha tersebut bisa terkontrol dengan baik. Oleh sebab itu diperlukan sistem yang dapat membantu meramalkan penjualan herbisida dari waktu ke waktu. Sehingga dengan hasil peramalan yang dihasilkan, diharapkan bisa membantu penjualan sesuai dengan kondisi yang ada. Adapun metode yang akan dipakai untuk penelitian yaitu metode  Single Exponential Smoothing. Kata kunci :  Penjualan; peramalan; pertisida; single exponential smoothing; sistem.